Implementation of Key Components of Evidence-Based Family Therapy for Eating Disorders in Child and Adolescent Psychiatric Outpatient Care - Wallin, Ulf; Saha, Sanjib (Frontiers in Psychiatry, 2020)
Background: Restrictive eating disorders with pronounced starvation is serious psychiatric conditions that often begin during childhood or adolescence. An early and efficient intervention is crucial to minimize the risk of the illness becoming longstanding and to limit the consequences. There is good evidence that weight gain during the first month of treatment goes with a better prognosis. Only a limited amount of young people suffering from severe restrictive eating disorder receive an evidence-based treatment at present in Sweden. The ROCKETLAUNCH project intends to implement key components of the evidence-based family therapy during the first month of treatment in Child and Adolescent Psychiatric outpatient care. Methods: From the southern part of Sweden, 12 local Child and Adolescent Psychiatric outpatient clinics will take part. All patients with a restrictive eating disorder and pronounced starvation together with their families will be asked to take part in the study. We expect that one hundred fifty patients will be assessed every year. The patients and their families will receive one month of intense manualized treatment. Bodyweight, days in inpatient care, eating disorder and other psychopathology-related symptoms, will be evaluated after one month and at 12-month follow-up. Economic evaluation of ROCKETLAUNCH will also be carried out alongside the intervention. At each outpatient clinic, data from the 10 previous patients will be gathered to compare the treatment provided at ROCKETLAUNCH with the standard treatment in Sweden. Discussion: We expect that by implementing the key components of the evidence-based family therapy during the first month of treatment, the prognosis of young newly diagnosed patients with severe restrictive eating disorders, primarily anorexia nervosa will improve, which, in turn, will reduce the need for psychiatric inpatient care. Trial registration: ClinicalTrials.gov, NCT04060433. Registered on 27 August 2019.